2013
DOI: 10.1155/2013/364247
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Procedural Plaque Embolisation in Native Coronary Arteries: Pathophysiology, Diagnosis, and Prevention

Abstract: The detachment of atherothrombotic material from the atherosclerotic coronary plaque and downstream embolisation is an underrecognized phenomenon and it causes different degrees of impairment of the coronary microcirculation. During treatment of obstructive atherosclerotic plaque by percutaneous coronary intervention (PCI) distal embolisation (DE) is considered to be inevitable and it is associated with potential clinical and prognostic implications. This review aims to assess the main aspects of both spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 137 publications
0
12
0
Order By: Relevance
“…This condition is well known as no reflow and is mainly related to a profound impairment of coronary microvasculature secondary to ischaemia/reperfusion injury and distal embolisation 28. The advocated mechanisms of action of PICSO make it a very attractive device for application in limiting and eventually minimising the impact of no reflow.…”
Section: Clinical Setting For Potential Successful Applications Of Csimentioning
confidence: 99%
“…This condition is well known as no reflow and is mainly related to a profound impairment of coronary microvasculature secondary to ischaemia/reperfusion injury and distal embolisation 28. The advocated mechanisms of action of PICSO make it a very attractive device for application in limiting and eventually minimising the impact of no reflow.…”
Section: Clinical Setting For Potential Successful Applications Of Csimentioning
confidence: 99%
“…Furthermore, coronary microemboli is considered to be inevitable during PCI revascularization of obstructive atherosclerotic plaque [62], because plaques and debris are disrupted during the passage of guide-wires, positioning of the balloon and stent implant. Differentiation of spontaneous from procedural microembolization is difficult because patients arrive to the hospital with pre-existing AMI related to coronary thrombi and PCI revascularization is also associated with microthrombi.…”
Section: Coronary Microembolimentioning
confidence: 99%
“…Galiuto classified microvascular damage after revascularization into structural (irreversible) and functional (reversible), where the structural damage is related to damage of microvascular walls; conversely, the functional damage is related to edema and cellular plugging [101]. De Maria et al showed the similarity in the sequelae of spontaneous and procedural distal microembolization [62]. Jaffe et al described two pattens of MVO, namely zonal MVO located in the core of pre-existing infart (primery PCI) and patchy MVO located in ischemic myocardium (elective PCI) [44].…”
Section: Microvascular Obstruction and Microinfarctionmentioning
confidence: 99%
“…Although the management of coronary artery disease (CAD) has developed and improved dramatically during the past two decades, CAD is still a disease with increasing morbidity and mortality posing a major threat to human's health [1,2]. e pathogenesis of CAD includes several mechanisms [3], such as lipid metabolism [4,5], inflammatory response [6,7], and activation of the coagulation and fibrinolysis system [8]. Alanine aminotransferase (ALT) is referred as liver transaminase and predominantly expressed by hepatocytes.…”
Section: Introductionmentioning
confidence: 99%